A study of prevalence and antimicrobial resistance and pathogenic activity of bacteria in the air of Dhaka city - Nawar, Shaeri; Rashid, Maliha Tabassum (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2019.